Effectiveness of Physical Fitness Training with the B4Fit Model - Lili Bile, Robertus; Bayo Ola Tapo, Yohanes; Fromantius Bali, Yohanes (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2024)
This study aims to evaluate the effectiveness of physical fitness training for students of the Physical Education, Health and Recreation (PJKR) Study Program at STKIP Citra Bakti using the B4FIT Model. The research method used is a time series pre-experiment involving 40 PJKR students as research samples who undergo a physical fitness training program with the B4FIT Model. The main stages of the study included identification of variables to be measured, design and implementation of the exercise program, and data collection through pre- and post-intervention physical tests. The results showed a significant improvement in the physical fitness level of students who underwent training with the B4FIT Model. Variables such as muscular strength, agility, and cardiorespiratory endurance showed consistent and meaningful improvements after the intervention. From these findings, it is concluded that the B4FIT Model is effective in improving the physical fitness level of PJKR students at STKIP Citra Bakti. The implementation of exercise programs with this approach is able to have a positive impact on the physical fitness aspects of students. The implications of this study support the need for a structured fitness training method that can improve the health and physical performance of PJKR students.